Enhanced Deep Learning Based Predictive Analysis of Electricity Power Consumption Forecasting for Maharashtra State Electricity Distribution Company Ltd. (MSEDCL) - Kanchan A. Khedikar ,Dr.Piyush Kumar Pareek (Journal of Computational Analysis and Applications (JoCAAA), 2024)
Accurate forecasting of electricity power consumption is vital for efficient grid operation, optimal resourcemanagement, and sustainable energy planning. Energy consumption analysis involves gathering, evaluating, and interpretingdata on energy usage—particularly electricity. Our research centers on forecasting energy demand for Maharashtra StateElectricity Distribution